2016
DOI: 10.1212/wnl.0000000000002462
|View full text |Cite
|
Sign up to set email alerts
|

Standardized EEG interpretation accurately predicts prognosis after cardiac arrest

Abstract: Objective:To identify reliable predictors of outcome in comatose patients after cardiac arrest using a single routine EEG and standardized interpretation according to the terminology proposed by the American Clinical Neurophysiology Society.Methods:In this cohort study, 4 EEG specialists, blinded to outcome, evaluated prospectively recorded EEGs in the Target Temperature Management trial (TTM trial) that randomized patients to 33°C vs 36°C. Routine EEG was performed in patients still comatose after rewarming. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
395
9
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 317 publications
(439 citation statements)
references
References 41 publications
18
395
9
11
Order By: Relevance
“…Indeed, studies using continuous EEG monitoring and consensus definitions have shown that EEG had the best predictive value at 12 and 24 h after ROSC [40,42,43]. A normal voltage, continuous EEG devoid of periodic or epileptiform discharges (referred to as ''benign'' EEG) at 12 h or, to a lesser extent, at 24 h after ROSC is most often associated with good recovery [42] (Fig. 1a).…”
Section: Eeg Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, studies using continuous EEG monitoring and consensus definitions have shown that EEG had the best predictive value at 12 and 24 h after ROSC [40,42,43]. A normal voltage, continuous EEG devoid of periodic or epileptiform discharges (referred to as ''benign'' EEG) at 12 h or, to a lesser extent, at 24 h after ROSC is most often associated with good recovery [42] (Fig. 1a).…”
Section: Eeg Backgroundmentioning
confidence: 99%
“…1a). On the contrary, a suppressed (\10 lV) or suppression-burst (including generalized periodic discharges on a suppressed background) background (referred to as ''highly malignant'' EEG) at 24 h is associated with lack of neurological recovery [42][43][44] (Fig. 1b-e).…”
Section: Eeg Backgroundmentioning
confidence: 99%
“…Specifically, bilateral absence of brainstem reflexes, absence of motor response to pain and treatmentresistant myoclonus (7-10) unreactive or discontinuous EEG background activity (10)(11)(12) bilateral absence of N20 Somatosensory Evoked Potentials (SSEP) (7) and high serum Neuron Specific Enolase (NSE) (13) are related to poor neurological recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Some methods, notably SSEP, have high specificity to predict poor outcome but limited sensitivity to identify patients with severe brain injury 5. Other methods, such as EEG6 and neuroimaging,7 appear more sensitive but may be prone to interpreter variability 8…”
mentioning
confidence: 99%